Analysis of the Effect of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Return on Equity Towards Profit Planning at PT Mina Mulia Perkasa - Ardian, Noni (Journal of Community Research and Service, 2022)
The more effective the profit planning, the greater the company's net profit. High profit planning demonstrates the company's ability to create value for its shareholders. The company's success in developing this value undoubtedly results in increased profits for its stockholders. This return is extremely important since it is used as a measure of the company's performance and as a basis for evaluating the future returns associated with expectations and risks. This study aimed to investigate and analyze the impact of CR on profits planning. To examine and assess the influence of DER on profit planning. To examine and assess TATO's impact on profit planning. To evaluate and analyze the impact of ROE on profit planning in the catering industry. To evaluate and assess the impact of CR, DER, TATO, and ROE on profit planning. This study employs quantitative data analysis, which involves testing and analyzing data by calculating numbers, followed by drawing conclusions from the test using descriptive statistical tests and multiple correlations. However, the data processing for this study is not performed manually, but rather through the use of Statistical Product and Service Solutions (SPSS). According to the study's findings, CR, TATO, DER, and ROE have a considerable influence on profit planning, both partially and simultaneously